Output and quality of cereal products from wheat varieties and wheat lines - Господаренко, Г. М.; Любич, В. В.; Полянецька, І. О. (Scientific Progress & Innovations, 2017)
The article presents the results of studying of anatomical content of grains of wheat varieties and lines, the yield and culinary evaluation of cereal products. It has been established that the high yield of cereals (85–89 %) and the high culinary score (7–9 points) has a grain of wheat varieties of soft Uzhynok, Vdala, Shchedra Nyva, Pannonikus, Emerino, Lupus, wheat lines of compact Umanchanka and lines obtained by hybridization Tr. aestivum/Tr. spelta. Extrusion of wheat grain significantly improves the culinary evaluation of the finished product due to the temperature treatment. Grain varieties Kohan, Vdala, Lupus, Emerino, Pannonikus, Ac Meckinon, Kulundinka, Umanchanka lines and wheat soft wheat lines are used for extrusion without peeling.